Implikasi Bentuk Perjanjian Kerja Terhadap Perlindungan Hukum Bagi Pekerja Pada Usaha Mikro dan Kecil - Sani Pratiwi, Alya; Pujiastuti, Endah; Arifin, Zaenal (JURNAL USM LAW REVIEW, 2024)
This research aims to understand and analyze the forms of work agreements implemented by micro and small enterprises, as well as the implications of the forms of work agreements for legal protection for workers in micro and small enterprises. Every citizen has the right to have work and a decent life. To obtain work, workers need to have an employment relationship with the employer. This employment relationship occurs based on a work agreement made by the employer and the employee which can be made in writing or verbally. The work agreement contains the rights and obligations of both parties, therefore the work agreement is very important as a form of legal protection. It's just that in reality there are still many employment relationships that are not based on employment agreements, such as employment relationships in micro and small enterprises. The absence of a work agreement means that workers' rights and obligations are not fulfilled, and legal protection for them is not strong. The research method used is an empirical juridical method. The research results show that employers/employers make work agreements with their workers in verbal form for an indefinite period of time and do not make appointment letters for their workers. This has implications for legal protection for workers which becomes weak because there is no written proof of the agreement made. The use of verbal employment agreements in micro and small enterprises weakens legal protection for workers, thus policies are needed to encourage the implementation of written employment agreements to enhance legal certainty. Penelitian ini bertujuan untuk memahami dan menganalisis bentuk perjanjian kerja yang diterapkan oleh usaha mikro dan kecil, serta implikasi bentuk perjanjian kerja terhadap perlindungan hukum bagi pekerja pada usaha mikro dan kecil. Setiap warga negara berhak untuk memiliki pekerja dan kehidupan yang layak. Untuk memperoleh pekerjaan, pekerja perlu menjalani hubungan kerja dengan pemberi kerja. Hubungan kerja tersebut terjadi atas perjanjian kerja yang dilakukan oleh pemberi kerja dengan pekerja yang dapat dibuat secara tertulis atau lisan. Di dalam perjanjian kerja termuat hak dan kewajiban kedua belah pihak, oleh karena itu perjanjian kerja sangat penting sebagai suatu bentuk perlindungan hukum. Hanya saja pada kenyataannya masih banyak hubungan kerja yang tidak didasarkan pada perjanjian kerja, seperti pada hubungan kerja di usaha mikro dan kecil. Ketiadaan perjanjian kerja itu memungkinkan adanya hak dan kewajiban pekerja yang tidak terpenuhi, serta perlindungan hukum bagi mereka tidak kuat. Metode penelitian yang digunakan adalah metode yuridis empiris. Hasil penelitian menunjukan bahwa pengusaha/pemberi kerja membuat perjanjian kerja dengan pekerjanya dalam bentuk lisan untuk waktu tidak tertentu dan tidak membuat surat pengangkatan untuk pekerjanya. Hal ini berimplikasi terhadap perlindungan hukum bagi pekerja yang menjadi lemah karena tidak ada bukti tertulis dari kesepakatan yang dibuat. Penggunaan perjanjian kerja lisan pada UMK melemahkan perlindungan hukum bagi pekerja, sehingga diperlukan kebijakan yang mendorong penerapan perjanjian kerja tertulis untuk meningkatkan kepastian hukum.